Evaluation of the Impact of Stunting Policy in Improving Nutrition in Banyumas Regency - Amud Sunarya; Milwan; Jayanti Armida Sari (Yayasan Ilomata, 2026)
This study examines the effectiveness of Banyumas Regent Regulation Number 25 of 2020 in reducing stunting prevalence in Banyumas Regency, where stunting remains a critical public health and development issue. The research question is: How effective is the regulation in reducing stunting prevalence through targeted nutritional interventions. A mixed-methods approach was employed, combining quantitative survey data from families with toddlers and qualitative interviews with key stakeholders to assess policy implementation and outcomes. The findings show a significant decline in stunting prevalence in 2022 following the regulation’s implementation, although an increase in 2023 indicates sustainability challenges. Unlike national-level policy frameworks that provide broad strategic guidelines and standardized targets across regions, this regional regulation translates national priorities into context-specific interventions tailored to local demographic, socio-economic, and institutional conditions in Banyumas. Compared to other local case studies that often focus on program-level initiatives or pilot projects, this regulation represents a formalized and binding district-level legal instrument that integrates cross-sector coordination, budget allocation, and monitoring mechanisms within the local governance structure. The study concludes that while the regulation demonstrated initial effectiveness, sustained stunting reduction requires stronger program implementation, cross-sector coordination, and continuous policy support to ensure long-term impact at the regional level.